MANAJEMEN STRATEGI DALAM PENCEGAHAN PERNIKAHAN USIA DINI DI KOTA PEKANBARU - Silvia Waliddra; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Early marriage in Indonesia is increasing from year to year. This problem has an impact on the quality of children, family, family harmony and divorce. This is also the reason why children drop out of school. In addition, in Pekanbaru City, early marriage is also rife, even though Law No. 16 of 2019 has been enacted, that the minimum age limit for marriage for both men and women is 19 years. It was from this background that this research was conducted. The purpose of writing a thesis is to find out what is behind the occurrence of early marriage in Pekanbaru City. The theory put forward by Hunger and Wheleen (2003:11) is Environmental Observation, Strategy Formulation, Strategy Implementation, Evaluation and Control. This study used the method documentation, data analysis and interviews. Secondary data obtained from related government agencies, books, journals or data from the internet which contains related theories or research results. The results of this study explain that the strategy of the Pekanbaru City Women's Empowerment and Child Protection Service has not been successful because the early marriages that occur are motivated by the community environment and family environment. The lack of control of the surrounding community has resulted in changing norms and the emergence of a free culture as well as a lack of cooperation between the Pekanbaru City Women's Empowerment and Child Protection Service and PATBM. Keywords : Strategic Management, Age Limit for Marriage, Early Marriage